Value Added Determinants Analysis Of The Fish Rengginang Micro Industry In Situbondo District - Moh. Rasidi; Ramli (Institute of Computer Science (IOCS), 2022)
Processing of fish rengginang will have an economic impact, when it has high added value. The objectives of this study include 1) knowing the added value of fish rengginang and 2) knowing the effect of selling prices, raw material prices, other raw material prices and the average salary on the added value of fish rengginang. Value added analysis uses hayami calculation and value added determinant analysis uses multiple regression analysis. The results showed that 1) the added value of fish rengginang varied, namely an average of Rp. 7,745 per kilogram, the average value added ratio is 33%, the average profit is Rp. 7,190 per kilogram and the average profit is 32,96%, 2) The results of the F-test show that there is a significant influence between the selling price, the price of raw materials, the price of other raw materials and the average salary together on the added value. The results of the t-test indicate that there is a significant effect between the selling price, the price of raw materials, the price of other raw materials and there is no significant effect between the average salary separately on the added value.